A Post-Mortem Study of “Lifelines”: Common Belief Vs. Reality - Sandip Mukhopadhyay; Sayak Sovan Dutta; Shelly Samanta (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Dermatoglyphicsis the scientific study of naturally occurring creases on certain body partslike palms, fingers, soles and toes.As per Dermatoglyphics, the creases are believed to result from flexionof the fetal skin and can be influenced by factors causing aberrant development of the embryo. Method: theobjectives of the study was to examining the length of lifelines of the deceased and calculation of predictedage of individuals from their lifeline’s length by applying the knowledge of palmistry. And to compare thepredicted age with the age at death of those deceased individuals. 100 cases all above 18 years are studiedover a period of three months. Conclusion: The result of this study revealed that it is not in agreement withthe popular belief of Palmistry among most of the common people that length of lifeline reveals longevity.More is the age at death, the likelihood of the prediction of longevity from the lifeline being right is more.